PENGARUH TINGKAT KEPERCAYAAN DAN KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN SHOPEE PAYLATER PADA GENERASI GEN Z - Putri Nabila Harahap (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This research aims to see and show how trust and convenience influence purchasing decisions using Shopee Paylater in generation Z. The research method used is a quantitative method. Quantitative methods are research methods that aim to determine the relationship between two or more variables and the data is expressed in numerical form and uses statistical analysis techniques. The research results show that the trust level variable does not have a significant effect and has a positive relationship on the decision to use Shopee Paylater. This positive relationship shows that as the level of trust increases, the decision to use Shopee Paylater also increases, but the relationship between these two variables is not significant. The convenience level variable has a significant influence and has a positive relationship on the decision to use Shopee Paylater. This positive relationship shows that as the level of convenience increases, the decision to use Shopee Paylater also increases. The variables of trust and convenience simultaneously have a significant influence on the decision to use Shopee Paylater.